Recently Formed Crater Clusters on Mars. Issue 4 (8th April 2019) - Daubar, I. J.; Banks, M. E.; Schmerr, N. C.; Golombek, M. P.
Abstract: This study maps and measures assorted properties of new dated crater clusters that formed recently when impactors fragmented in the atmosphere of Mars. We report these statistics for 77 clusters: number of craters, size of cluster, dispersion of cluster, direction (azimuth) from which the impactor approached, and an estimate of the angle from vertical of the impact. Clusters range from a few to hundreds of craters, with most containing tens of craters. They are most commonly dispersed over hundreds of meters, with extents ranging from a few meters to a few kilometers. We find that dispersion generally does not correlate with topographic elevation. However, when the highest elevations are disregarded, clusters are more dispersed at lower elevations, as expected. Impact azimuths are randomly distributed and do not express a clear directionality of incoming meteoroids. Results suggest impacts occur closer to horizontal than expected, which could be due to observational effects. The characteristics we report here provide important constraints for future work in understanding atmospheric fragmentation processes; properties of the impactors themselves, such as density and orbital parameters; and the seismic detectability of impacts. These are critical aspects to understand, as approximately half of current impacts are observed to be clusters. Plain Language Summary: We studied clusters of new craters that formed in the last few years when meteoroids broke up in the atmosphere of Mars. We studied 77 clusters and measured the number of craters, the sizes of the clusters, how spread out the clusters are, the direction the impactors came from, and the angle of the impacts. Clusters range from a few to hundreds of craters, with most containing tens of craters. They are usually spread out over hundreds of meters, ranging from a few meters to a few kilometers. Except for the highest areas, clusters are more spread out at lower elevations, as expected. Impactors come from all different directions. Impacts are closer to horizontal than expected. This information will be used to understand breakup in the Martian atmosphere; properties of the incoming meteoroids, such as their density and orbits; and how well we would be able to detect impacts with a seismometer. This is important because about half of current impacts at Mars are clusters. Key Points: We report on properties of new dated crater clusters on Mars; most clusters in this study comprise <10 craters and span hundreds of meters Crater cluster dispersion increases for lower elevations when highest elevations are disregarded; impact azimuths are randomly distributed Impact angles are shallower than expected, which could be a possible observation effect